Measuring the Satisfaction Levels of Customers of Fresh Vegetables towards the Marketing Mix in Traditional Markets in Sukoharjo Regency, Indonesia - Raya Ilham Syah Majiid; Joko Sutrisno; Umi Barokah (Caraka Tani: Journal of Sustainable Agriculture, 2020)
Vegetables are horticultural crops that have a high market absorption. Modern market that is considered to have many advantages does not necessarily reduce consumers’ shopping interest at traditional markets. Traditional markets appear to have different characteristics and visitor segments from modern markets. This study aims to determine the level of consumers’ satisfaction of vegetables towards the marketing mix in the traditional markets in Sukoharjo. Data were processed using the Customer Satisfaction Index (CSI) method. The study was conducted from January to March 2019 with 80 consumers of vegetables as the respondents taken using quota sampling technique. CSI analysis was used to measure the level of customers’ satisfaction by calculating the rates of indicator performance attached to the items/services given by the consumers. Based on the CSI values, the result of the study conclude that consumers were satisfied with the services provided in traditional markets, which put priority on using family system to create convenient atmosphere of transactions.